2012
DOI: 10.1063/1.4774037
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of lithium clusters by electronic stress tensor

Abstract: We study the electronic structure of small lithium clusters Lin (n = 2 ∼ 8) using the electronic stress tensor. We find that the three eigenvalues of the electronic stress tensor of the Li clusters are negative and degenerate, just like the stress tensor of liquid. This leads us to propose that we may characterize a metallic bond in terms of the electronic stress tensor. Our proposal is that in addition to the negativity of the three eigenvalues of the electronic stress tensor, their degeneracy characterizes s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 52 publications
2
48
0
2
Order By: Relevance
“…In order to determine the atomic configurations of the Li n clusters, we take first the initial atomic configuration from previous theoretical calculations [9,12,13,10,23,24] and then we fully relax these structures within the DFT calculations. Both the SVWN and B3LYP approximations are used for the cluster structure relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the atomic configurations of the Li n clusters, we take first the initial atomic configuration from previous theoretical calculations [9,12,13,10,23,24] and then we fully relax these structures within the DFT calculations. Both the SVWN and B3LYP approximations are used for the cluster structure relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we have proposed that the negativity of the three eigenvalues of the stress tensor and their degeneracy, which is the same pattern as liquid, can characterize some aspects of the metallic nature of chemical bonding. [32,42] In Ref. [42], it has been shown that the three eigenvalues of the Li and Na clusters have almost same values while the hydrocarbon molecules have the largest eigenvalue much larger than the second largest eigenvalue, which has similar value to the smallest eigenvalue.…”
Section: Electronic Stress Tensor and Its Eigenvaluesmentioning
confidence: 99%
“…In order for efficient material search, it is important to characterize the chemical bonding of the lithium ionic conductors through the quantum chemical electronic structure calculation, and establish the connection with their material properties like chemical stability, diffusivity, and so on. We have been developing the characterization scheme of electronic structure using the electronic stress tensor density and kinetic energy density based on the rigged quantum electrodynamics (RQED) theory, and have applied it to various quantum systems . As a preliminary stage of our research, we have applied our method to the crystal structures of Li3PO4 and Li3PS4.…”
Section: Introductionmentioning
confidence: 99%